Experiences in sub-Saharan Africa with GM crop risk communication - Racovita, Monica; Obonyo, Dennis Ndolo; Anguzu, Robert; Bamwenda, Gratian; Kiggundu, Andrew; Maganga, Harrison (GM crops & food, 2013)
In tackling agricultural challenges, policy-makers in sub-Saharan Africa (SSA) have increasingly considered genetically modified (GM) crops as a potential tool to increase productivity and to improve product quality. Yet, as elsewhere in the world, the adoption of GM crops in SSA has been marked by controversy, encompassing not only the potential risks to animal and human health, and to the environment, but also other concerns such as ethical issues, public participation in decision-making, socio-economic factors and intellectual property rights. With these non-scientific factors complicating an already controversial situation, disseminating credible information to the public as well as facilitating stakeholder input into decision-making is essential. In SSA, there are various and innovative risk communication approaches and strategies being developed, yet a comprehensive analysis of such data is missing. This gap is addressed by giving an overview of current strategies, identifying similarities and differences between various country and institutional approaches and promoting a way forward, building on a recent workshop with risk communicators working in SSA.
Keywords: Public participation; Scientists; Risk communication; Capacity-building needs; Expertise